The Effect of Using a Project-Based Learning Model Assisted by Creative Media on Increasing Student Interest in Learning - Fatwa, Baiq Radiatul; Sahrul, Adhi; Haliq, Agil Syahrial; Fadillah, Rozi; Saputri, Tri; Herianto, Edy (CV. Rayyan Dwi Bharata, 2024)
The purpose of this study is to see the impact of the implementation of project-based learning supported by creative media can influence students' interest in and outside the classroom to learn. class to learn. The study involved 50 students from SMPN 21 Mataram, who were divided into two different groups: an experimental group and a control group. experimental and control groups. The researcher used a questionnaire to obtain data on students' interest in learning. The instrument has been tested for validity and reliability. Before conducting hypothesis testing, the researcher Researchers conducted a prerequisite test on the research data. Prerequisite test through homogeneity test using Levene test while, for the normality test the statistical formula used is the Kolmogorov-Smirnov Test and Shapiro-Wilk.The results are the basis for hypothesis testing using the Hypothesis testing using the Mann Whitney U Test with non-parametric tests with conclusions conclusion which confirms that there is an influence regarding the application of PjBL on increasing students' students' interest in learning which is statistically proven through the acceptance of Ha (Asymp.Sign value of 0.001 0.05), it can be concluded that the Alternative Hypothesis is accepted. The results of this study indicate that the use of creative media in project-based learning is significantly The results of this study indicate that the use of creative media in project-based learning significantly increases students' interest in learning. in learning. The findings of this study strongly support the idea that the use of project-based learning creative project-based learning can be an efficient method to develop students' drive and students' interest in learning at school